A Study on The Second Year Students’ Ability to Comprehend Reading Text Based on The Level of Comprehension Questions at SMAN 1 Sijunjung - Yessy Marzona (Fakultas Sastra Universitas Ekasakti, 2021)
This research was designed to describe the ability of the second year students to comprehend reading text according to the levels of question at SMAN 1 Sijunjung. To be more specific it aimed at describing students’ ability to comprehend reading text according to the levels of comprehension questions. This research was descriptive research. The population of this research was the second year students at SMAN 1 Sijunjung. The number of members of population was 165 students. The researcher took 80 students as the sample. In selecting sample, the researcher used stratified cluster random sampling technique. The data of this research were the students’ scores on comprehending text according to the levels of question. To take the data, the researcher used reading test. In analyzing the data, there were some steps she used: the first was presentation of raw scores and calculation of Mean and Standard Deviation. The second was classifying the students’ ability into high, moderate, and low ability. The third was determining the percentage of the students who had high, moderate, and low ability. The result of the data analysis showed that the ability of the second year students to comprehend reading text according to the levels of question at SMAN 1 Sijunjung was moderate. It was proved by the fact that 41 students (51.25%) had moderate ability. Specifically, the ability of the students to comprehend reading text at the level of comprehension questions was moderate. . It was proved by the fact that 55 students (68.75%) had moderate ability. Based on the findings above, it was suggested that the teachers give more exercises, beginning from the low levels of question to the high levels of question. It was also suggested to the teachers that they must promote a discussion to answer the questions on the texts being taught.